TERRITORIAL REGULATION OF THE DUTCH COLONIAL GOVERNMENT IN NEDERLANDS NIEUW GUINEA 1898-1962 (Paramita: Historical Studies Journal, 2013)
This study discussed about the regulation of the Dutch colonial administration for its expansion in Nederlands Nieuw Guinea (NNG) between 1898 and 1962.  The arrangement covered the expansion area, uniting and abolition of the government. This process began with the exploration activities, construction of infrastructure facilities and transportation/communication and recruitment of government officials. Construction of transportation and communication made local economy was increase. Government officials who stationed in the region must meet the specific requirements such as familiar with the area and experienced in their duties as well as having a high spirit of devotion. Territorial structuring was based on consideration of geographic/transportation access, culture, economic and political values of such area. Government policy on regional growth aims to shorten the span of colonial government control over territory and population of NNG and government's services that closer to the territory’s population.Key words: Territorial regulation, expansion, NNG  Penelitian ini mengkaji tentang peraturan pemerintahan kolonial Belanda atas segala bentuk ekspansi di Nederlands Nieuw Guinea (NNG) pada tahun 1898 dan 1962. Peraturan ini meliputi perluasan wilayah, menyatukan dan penghapusan pemerintah. Proses ini dimulai dengan kegiatan eksplorasi, pembangunan fasilitas infrastruktur dan transportasi / komunikasi dan perekrutan pejabat pemerintah. Pembangunan transportasi dan komunikasi membuat perekonomian lokal meningkat. Pejabat pemerintah yang ditempatkan di wilayah tersebut harus memenuhi persyaratan tertentu seperti akrab dengan daerah dan berpengalaman dalam tugas-tugas mereka serta memiliki semangat  pengabdian tinggi. Penataan wilayah didasarkan pada pertimbangan geografis / akses transportasi, budaya, ekonomi dan nilai-nilai politik daerah tersebut. Kebijakan pemerintah mengenai pertumbuhan regional bertujuan untuk memperpendek rentang kendali pemerintah kolonial atas wilayah dan penduduk NNG dan jasa pemerintah yang lebih dekat dengan penduduk wilayah itu. Kata kunci: pearaturan teritorial, perluasan wilayah, NNG